THE DIFFERENCES OF KNOWLEDGE AND ATTITUDE RELATED COVID-19 BETWEEN RURAL AND URBAN COMMUNITIES - Nadia Oktiffany Putri; Anang Nurwiyono (Jurnal Keperawatan Malang, 2022)
Background: Covid-19 stands for Coronavirus disease 19. The Covid-19 pandemic as of April 2020 has been confirmed to have reached more than 4.3 million cases and 290,000 deaths worldwide. In Indonesia, the total number of Covid-19 cases per October 2020 was 392,934. Various efforts to prevent the spread of Covid-19 infection have been socialized. However, the phenomenon shows that Covid-19 cases are still increasing. One of the factors that allow this condition is a violation of health protocols. In this pandemic situation, there are still few studies that discuss knowledge, attitudes, and practices about Covid-19 among residents in rural and urban areas. Aim: The aim of this study was to determine the differences of knowledge and attitudes about Covid-19 in rural and urban communities. Methods: This study was a quantitative study using analytical descriptive design with a cross sectional approach. Results: The results stated that there was a significant difference between the knowledge of rural and urban communities with a p-value (0.017) <0.05. The p-value (0.899) > 0.05 in the attitude variable showed if there was no significant difference between rural and urban communities. Conclusion: In conclusion, the findings highlight that knowledge about Covid-19 in rural communities needs to be improved and attitudes to prevent transmission need to be increased in urban and rural areas.